2018
DOI: 10.1111/1365-2745.13015
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence and the niche in a nurse–cactus interaction: Is cyclic dynamics justified?

Abstract: The interaction between the nurse plant Larrea tridentata and the cacti Cylindropuntia leptocaulis is thought to follow cyclical‐replacement dynamics. However, the required changing nature of their interaction, from facilitation to competition, has not been investigated through their full life cycle. In order to test the hypothesised cyclical dynamics, we compared the demography of four subpopulations (LA = Larrea associated to Cylindropuntia; CA = Cylindropuntia associated to Larrea, LS = solitary Larrea; CS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…Individuals that grew more generally had higher mortality when considering all ages, indicating a trade-off between growth and survival [43,44]. Interestingly, the effect was reversed for ages above 10 (i.e., from reproductive maturity).…”
Section: Discussionmentioning
confidence: 98%
“…Individuals that grew more generally had higher mortality when considering all ages, indicating a trade-off between growth and survival [43,44]. Interestingly, the effect was reversed for ages above 10 (i.e., from reproductive maturity).…”
Section: Discussionmentioning
confidence: 98%
“…According to Valiente-Banuet and Verdú (2007), regeneration niche traits are conserved throughout evolution, i.e., similar species require similar conditions to germinate and establish themselves and, therefore, phylogenetically distant species grow under the canopy of nurse species, and not of similar species and much less of the same species. Facilitation between distant species can be easily observed when studying shrub species facilitating cactus species (e.g., Valiente-Banuet et al, 1991;Drezner, 2006;Flores-Torres et al, 2019). Although in our work we studied species with the same growth form and with a certain phylogenetic relatedness, facilitation was also Tavares et al found in species of the same family (Fabaceae, the more distantly related pair).…”
Section: Discussionmentioning
confidence: 49%
“…For instance, in some studies, the elucidation of environmental effects, plant-plant interactions and coexistence mechanisms would have been muddled by the inclusion of density dependence in the model (Verhulst et al 2008, Ferrer et al 2015, Flores-Torres et al 2019. Topping et al (2015) advocate the use of biological narratives when considering what to include, and how to include it, in a model.…”
Section: O N L I N E F I R S Tmentioning
confidence: 99%